THE EFECT OF DIALOGUE TOWARD SPEAKING SKILL AT SECOND GRADE SMA MUHAMMADIYAH - Zahera, Rifka; Rasyidah, Ummi; Rahayu, Pipit (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
The purpose of this research Intention of this research were ( 1) to know was communications of throughdialoguing could improved ability converse student in english and ( 2) to know how applying from the techniquecan improve the ability of studentsâ speaking. This research carried out in SMA Muhammadiyah whererespondent from this research were students of class of XI 2 as control class (24 student) and XI 1 as experimentclass ( 22 student). Invention indicate that there was important effect between instruction of oration withdialogue technique. That was visible from value t0 ( t-test)= 74.5000 bigger than tt(ttable) 5%= 2,00 with use ttest.That was inferential that there was effect influence speaking of students through dialogue technique